PELAKSANAAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) TERHADAP PEKERJA DI BIRO UMUM PERENCANAAN DAN KEUANGAN (BUPK) UNIVERSITAS NEGERI YOGYAKARTA - , FADHIL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The employment agreement is the beginning of the birth of the industrial relations between employers or employers with workers. In recent years, many employers who use Specific Time Work Agreement (PKWT) to reduce labor costs in order to reduce the salary component for employees. It's just that in practice many application systems Specific Time Work Agreement (PKWT) that is not in accordance with the provisions of Law No. 13 Year 2003 concerning Manpower, to the detriment and eliminate the protection of workers / laborers. This study aims to find out about the implementation of the employment agreement specified time (PKWT) committed against workers who worked at the General Bureau of Planning and Finance (BUPK) Yogyakarta State University. This study is a descriptive analysis with empirical juridical approach, whereas the data obtained through library research and field research. Furthermore, the data were analyzed qualitatively. From the results of this study concluded, the legal basis used for recruiting and working with the system employment agreement specified time (PKWT) is Rector No. regulation. 03 of 2012 which regulates the system of recruitment of workers with a contract system. And in the implementation of systems specified time employment agreement (PKWT) there are some irregularities such as lack of health insurance, severance pay, and the work being done should be tied to a specific time employment agreement system (PKWTT). In the implementation of health insurance should be considered and provided for workers in the Bureau of Planning and public finance (BUPK) and the regulations made rector pay more attention to both parties, both employers workers themselves. Key Note : Implementation Agreement - PKWT